Investors' Heterogeneity, Prices, and Volume around the Ex-Dividend Day - Michaely, Roni; Vila, Jean-Luc (Journal of Financial and Quantitative Analysis, 1995)
This paper analyzes the relationship between tax heterogeneity and the behavior of stock prices and volume around the ex-dividend day within an equilibrium framework.We conclude that, even in a world without transaction costs, the price drop on the ex-day need not be equal to the dividend amount.The model allows us to account for higher market trading volume around the ex-day.The market trading volume is shown to be a positive function of tax heterogeneity among traders.We show that the volume of trade around the ex-day contains information about investors' tax preferences above and beyond the information contained in the ex-day price alone.Consistent with the model's predictions, our empirical analysis reveals that as the risk associated with the ex-dividend day increases, or tax heterogeneity decreases, trading volume decreases.constant), the abnormal volume of trade significantiy decreases.Using the period around the 1986 TRA, we are also able to show that a change in the degree of tax heterogeneity affects both prices and volume around the ex-dividend day.Our analysis shows that unless a perfect tax clientele exists, it is not possible to infer tax rates from price alone.[By a perfect tax clientele we mean that each tax group hold different securities, and all trading is intra-group trading.See Miller and Modigliani (1961) and Elton and Gruber (1970)].However, the crosssectional distribution of tax rates can be inferred by using both price and volume data.This point can be illustrated using the following stylized example.Assume that there are three groups of traders in the marketplace with a marginal rate of substitution between dividends and capital gains income of 0.75, 1.0, and 1.25, respectively.Assume further that the average price drop relative to the dividend amount is 1.0.Using the standard analysis, we may conclude that the second group dominates the ex-dividend day price determination.However, this may not be the case.For example, suppose that 50% of the traders are from the first group, 50%